Counseling special populations in schools - Fisher, Emily S. (Oxford University Press, 2017)
"Counseling Special Populations in Schools provides school-based mental health professionals with practical, specific strategies for counseling special populations of students who are at risk for academic, social, emotional, and behavioral problems in school. These special populations include students who are homeless, living in foster care, involved with the juvenile justice system, LGBTQ, pregnant or parenting, gifted, in military families, at-risk for school failure and dropout, and impacted by incarcerated parents. Each chapter focuses on one group of students, highlighting critical background information and providing evidence-informed counseling approaches and strategies to promote resilience and support student development. Chapters provide specific information about how to use basic counseling skills, as well as more advanced counseling techniques such as Solution-Focused Brief Therapy, Cognitive Behavioral Therapy, and Motivational Interviewing, to address the needs and challenges of these special populations of students. This advanced-level counseling book is an excellent resource for mental health professionals and graduate students who want to be able to provide effective counseling services for all students. "--